CORRELATION BETWEEN GRAMMAR MASTERY AND WRITING SKILLS OF 4th-semester STUDENTS - Randy; Jamiluddin, Jamiluddin; Maf'ulah, Maf’ulah (e-Journal of ELTS (English Language Teaching Society), 2023)
The objective of this research is to find out the correlation between grammar mastery and writing skills. The researchers applied a correlational research design. There were two variables in this research, they were grammar mastery as variable X and writing skills as Variable Y. The researchers took the 4th-semester students as the population and the sample of this research. In selecting the sample, the researchers used a random sampling technique. 3 students from each class were taken randomly as the sample of this research. The total sample was 18 students. In conducting this research, the researchers used two tests. The tests were grammar and writing tests. A grammar test measured students’ competence in simple past tense. The test consists of 20 multiple-choice questions. The test is aimed at collecting data on students’ grammar mastery. In the writing test, the students chose one of three topics that were provided in the test’s instructions. The students wrote the text in the form of a recount text. The data were analyzed using Pearson Product Moment Correlation Coefficient. The result shows that the correlation coefficient between students’ grammar mastery and writing skills is 0.630. The result is categorized as substantial or high. It indicates that there is a positive correlation between grammar mastery and writing skills of 4th-semester students of the English Education Study Program of Tadulako University. It means that the students who have good grammar mastery also have good writing skills and the students who lack grammar mastery also have poor writing skills because grammar is one important aspect that influences students’ writing skills. The implementation of this finding in the teaching of writing skills is that the lecturers must find a way to integrate the teaching of writing skills with grammar.